DJ-1 regulating PI3K-Nrf2 signaling plays a significant role in bibenzyl compound 20C-mediated neuroprotection against rotenone-induced oxidative insult. (5th April 2017) - Zhang, Xiao-Ling; Yuan, Yu-He; Shao, Qian-Hang; Wang, Zhen-Zhen; Zhu, Cheng-Gen; Shi, Jian-Gong; Ma, Kai-Li; Yan, Xu; Chen, Nai-Hong
Graphical abstract: Highlights: 20C protects PC12 and SH-SY5Y cells against rotenone-induced oxidative injury. DJ-1 is necessary for 20C-mediated neuroprotection. 20C activates PI3K/Akt signaling and then promotes Nrf2 nuclear translocation. 20C may be developed as a novel candidate for alleviating the consequences of PD. Abstract: Oxidative stress is thought to be involved in the development of Parkinson's disease (PD). We previously reported that 20C, a bibenzyl compound isolated from Gastrodia elata, possesses antioxidative properties, but its in-depth molecular mechanisms against rotenone-induced neurotoxicity remains unknown. Recent studies indicate that without intact DJ-1, nuclear factor erythroid 2-related factor (Nrf2) protein becomes unstable, and the activity of Nrf2-mediated downstream antioxidant enzymes are thereby suppressed. In this study, we showed that 20C clearly protected PC12 and SH-SY5Y cells against rotenone-induced oxidative injury. Furthermore, 20C markedly up-regulated the levels of DJ-1, which in turn activated phosphoinositide-3-kinase (PI3K)/Akt signaling and inhibited glycogen synthase kinase 3β (GSK3β) activation, eventually promoted the nuclear translocation of Nrf2 and induced the expression of hemeoxygenase-1 (HO-1). The antioxidant effects of 20C could be partially blocked by ShRNA-mediated knockdown of DJ-1 and inhibition of the PI3K/Akt pathways with Akt1/2 kinase inhibitor, respectively. Conclusively, our findings confirm that DJ-1 is necessary for 20C-mediated protection against rotenone-induced oxidative damage, at least in part, by activating PI3K/Akt signaling, and subsequently enhancing the nuclear accumulation of Nrf2. The findings from our investigation suggest that 20C should be developed as a novel candidate for alleviating the consequences of PD in the future.